GOVERNMENTALITY: CASES OF THE RAYJA HOTEL CONFLICT CONSTRUCTION PERMIT, BUMIAJI SUB-DISTRICT, BATU - Friska Ayu O; Mardiyono ,; Andy Fefta Wijaya (Universitas Tribhuwana Tunggadewi, 2019)
Governance concept implies a shift in the role of the government, private sector and community, so that it necessary synergy in the implementation of the government. Community involvement in policy formulation needed to build the quality of local government. In reality, this ideal has not been able to be implemented in developing countries, in particular Indonesia. In Batu City, there is resistance against the construction of hotel residents who opposed the Rayja Local Regulation no. 7 of 2011 on Spatial Planning state that Sumber Gemulo is a protected area. Differences in knowledge caused a power space on each of the actors, in particular the Government. Space power it seeks to create a discourse by the main actor, Mayor. A series of regulatory practices that occur as a strategy of